Bio-catalyzed oxidation self-charging zinc-polymer batteries - Pan, Jun (2024)
Oxidation self-charging batteries have emerged with the demand for powering electronic devices around the clock. The low efficiency of self-charging has been the key challenge at present. Here, a more efficient autoxidation self-charging mechanism is realized by introducing hemoglobin (Hb) as a positive electrode additive in the polyaniline (PANI)-zinc battery system. The heme acts as a catalyst that reduces the energy barrier of the autoxidation reaction by regulating the charge and spin state of O2. To realize self-charging, the adsorbed O2 molecules capture electrons of the reduced (discharged state) PANI, leading to the desorption of zinc ions and the oxidation of PANI to complete self-charging. The battery can discharge for 12 min (0.5 C) after 50 self-charging/discharge cycles, while there is nearly no discharge capacity in the absence of Hb. This biology-inspired electronic regulation strategy may inspire new ideas to boost the performance of self-charging batteries.